IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN DALAM MEMBENTUK SIKAP WIRAUSAHA SISWA MA DARUSSALAM PUNCAK SILIRAGUNG BANYUWANGI - Nurkafidz Nizam Fahmi; Hafif Ferdiansyah (Institut Agama Islam Darussalam Blokagung, 2023)
The objectives set in this study are: (1) to determine the implementation of entrepreneurship education in shaping the entrepreneurial attitude of MA Darussalam Puncak Siliragung students; (2) to find out the form of implementing entrepreneurship education in shaping the entrepreneurial attitude of MA Darussalam Puncak Siliragung students. The methods used by researchers include a qualitative approach with descriptive research types. Data collection techniques use 3 stages, namely observation, interviews, and documentation. The data sources that the researchers obtained were primary data in the form of observations related to the implementation of student entrepreneurship education and entrepreneurial attitudes in madrasas/schools, interviews with school principals, teachers, and several students, as well as secondary data on documentation and activity archives from the institution. Checking the validity of the data by triangulation, namely triangulation of data, methods, and sources. Data analysis with interactive three models, namely data reduction, data presentation, and data verification. The results of his research: Implementation of Entrepreneurship Education in Forming Entrepreneurial Attitudes of MA Darussalam Puncak Siliragung Students include: (1) entrepreneurship planning is prepared based on vision, mission, curriculum, and areas of expertise, (2) planning of SKN (Real Work School) learning activities, (3) planning teaching and learning activities and their application into practice, the form of implementing entrepreneurship education in shaping the entrepreneurial attitude of MA Darussalam Puncak Siliragung students includes: (1) implementing learning and practice, (2) implementing student product marketing, (3) implementing SKN (Real Work School) activities ).